A Hydrogen‐Deficient Nickel–Cobalt Double Hydroxide for Photocatalytic Overall Water Splitting - Wang, Min; Wang, Jia‐Qi; Xi, Cong; Cheng, Chuan‐Qi; Zou, Cheng‐Qin; Zhang, Rui; Xie, Ya‐Meng; Guo, Zhong‐Lu; Tang, Cheng‐Chun; Dong, Cun‐Ku; Chen, Yong‐Jun; Du, Xi‐Wen (Angewandte Chemie International Edition, 2020)
Developing highly efficient and low‐cost photocatalysts for overall water splitting has long been a pursuit for converting solar power into clean hydrogen energy. Herein, we demonstrate that a nonstoichiometric nickel–cobalt double hydroxide can achieve overall water splitting by itself upon solar light irradiation, avoiding the consumption of noble‐metal co‐catalysts. We employed an intensive laser to ablate a NiCo alloy target immersed in alkaline solution, and produced so‐called L‐NiCo nanosheets with a nonstoichiometric composition and O2−/Co3+ ions exposed on the surface. The nonstoichiometric composition broadens the band gap, while O2− and Co3+ ions boost hydrogen and oxygen evolution, respectively. As such, the photocatalyst achieves a H2 evolution rate of 1.7 μmol h−1 under AM 1.5G sunlight irradiation and an apparent quantum yield (AQE) of 1.38 % at 380 nm. A single‐phase photocatalyst, a hydrogen‐deficient nickel–cobalt double hydroxide, was generated by laser ablation. This photocatalyst can drive overall water splitting under solar light irradiation in the absence of sacrificial agents and noble metal co‐catalysts because of its unique composition and structure, with partially removed hydrogen atoms as well as O2− and Co3+ ions exposed on the surface.